An empirical investigation on e-retailer agility, customer satisfaction, commitment and loyalty - Roy, Souvik; Raju, Amar; Mandal, Santanu (Business: Theory and Practice, 2017)
Internet has changed the way retailers do their business. They have gone electronic and are now termed as e-retailers. These e retailers face huge competition in securing their loyal customer base. In our study, we suggest that if e-retailers provide good information and system quality to their consumers and in turn show agility to resolve their issues, e-retailers may develop loyal customers. In our study, we propose a model to provide understanding of this process by studying the antecedents and consequences of e-retailers’ agility. Partial least squares were used for testing the proposed relationships. The empirical findings based on 222 completed responses suggest that information quality and system quality of e-retailer website can be a factor in consumers perceiving e-retailers to be agile. Also, this results in customer loyalty.